(3GdeYGdLGJ GdHbQGWjIs - (3GHbQGW GdMcjes ((3YKeGf Hf GdMSjf Hf YeQ s)
(3ChdgG (B:s
(3GdHGH GdChd ai UfYI GdUOQ heG jMhjg bO YRefG Cf fUa cd YVh fQjO Cf fPcQ GdYdI GdMGOKI ajg afTQM hUag hUhQJg s
(3BNQgG (B:s
(3hEfeG jSJNQL gPG ef bhI cdGe LGdjfhS hef GdChdi hGdCTHg ef SGFQ GdYdGLGJ JeJ GdebGdI GdYGTQI s
(3HChdg agQSs
(3jHOC GdeNWhW ef GdebGdI GdKGefI ef cJGH GdeYGdLGJ GdHbQGWjIs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs